Effectiveness of an Educational Program on Nurse's Knowledge and Practices Regarding Pain Management for Orthopedic Wards Patients in Baghdad Teaching Hospitals. - M. Abdul-Hamid, Alaa; H. Atiyah, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Background: Quazi-experimental study was carried out at the orthopedic wards in AL-Wasity Teaching Hospital, and Ghazi AL-Hariri Martyr Hospital for Surgical Specialties. Objectives: the study aim to assess nurses knowledge and practices regarding pain management for orthopedic wards patients in Baghdad teaching hospitals, assess effectiveness of an educational program on nurses knowledge and practices regarding pain management for orthopedic wards patients in Baghdad teaching hospitals, and find out the relationships between nurses knowledge and practices, and their socio-demographic characteristics (age, gender, level of education, years of employments in nursing, years of experience in orthopedic wards, and participation in training session). Methodology: data collected through the application of a pre-test/ post-test approach for the study group and control group through using of structured questionnaire and checklist. Data collection was done at two times: baseline data (before any intervention was provided to the study group) and 21 days after giving the educational program (in the study group). The period of the study was from 16th December 2019 to 6thApril 2020. A non - probability purposive sample was randomly selected from nurses who were working in orthopedic wards. The sample divided into two groups (20) nurses considered as study group, and another (20) nurses considered as control group. The study group was exposed to an educational program, while the control group was not exposed to the program. Descriptive statistical analysis procedure by using SPSS version 23 (frequency, percentage and mean of score and standard deviation) and inferential analysis procedure (person correlation coefficient and t-test and p-value) were used to analysis the data. Results: the results of this study shows that there is a highly significant differences related to nurses' knowledge and practices regarding pain management for orthopedic wards patients; between pre and posttest in the study group, whereas there is a minor difference between pre and posttest in the control group. Conclusion: Nurses' knowledge and practices regarding pain management for orthopedic wards patients has been improved after application of the educational program in the study group, which confirmed the effectiveness of the delivered program toward improving knowledge and practices regarding pain management for orthopedic wards patients, the study concluded that there is a significant association between nurses knowledge and practices and their socio-demographic characteristics in term of level of education and years of experience in orthopedic wards. Recommendation: The researcher recommended the necessity of continuing applying this program to a broader sample.